DFR – A New Model to Identifying Loyal Tourists on the Destination - SEDAGHAT, Shahrzad; DEHGHANI ZADEH, Mohammad Reza; AMIRI, Vahid (Journal of Environmental Management and Tourism, 2018)
Regarding the increasing tendency to travel in recent years, many cities offer more amusement plans to have the tourists visit them again. The importance of these plans is due to maintaining the current tourists, but not attracting the new ones. Hence, recognizing loyal tourists can reduce the expenses and flourish the tourism. Accordingly, in this research, we have attempted to develop a new model based on data mining techniques to reconnoiter loyal tourists more accurately. The presented model is named DFR and is based on the development of the well-known model RFM. In addition to DFR model, the Imperialist Competitive Algorithm (ICA) has been used to cluster the tourists. The DFR model was implemented on 1100 tourists visiting Shiraz between 2013 and 2015, show that this model has a higher accuracy than other existing models and has identified loyal tourists more precisely.